South African Christian Experiences From colonialism to democracy - Thomas Resane, Kelebogile (UJ Press, 2020)
Some of the studies in this publication excavate lost or disappearing indigenous toponyms. Those researchers contribute in a very concrete way to the preservation of indigenous toponyms, and thereby also the associated cultural heritage. The other papers explore how place naming functions as a mechanism with which to create mental maps and exert socio-political power.